Analisis Potensi Bahaya pada Pekerjaan dengan Metode Job Safety Analysis (JSA) di PT Sari Teknindo Perkasa Tahun 2024 - Ayunda, Mutiara; Sugriarta, Evino; Onasis, Aidil; Adriyanti, Sri Lestari; Awaluddin, Awaluddin (Jurnal Kesehatan Lingkungan Mandiri, 2024)
Potential hazards in industrial activities can cause work accidents. These hazards originate from humans, machines, materials and methods at work caused by the application of an occupational health and safety management system that is still not effective. Therefore, it is necessary to implement an OHS management system in recognizing potential hazards to prevent work accidents. The Job Safety Analysis (JSA) method can be applied in analyzing potential hazards at work then determining effective control measures to prevent risks that can occur. The purpose of this study is to determine the potential hazards, risk levels and hazard control measures at PT Sari Teknindo Perkasa in 2024. This type of research is descriptive with the object of research on the potential hazards of lathe, welding, grinding and scrap work. Potential hazards on the lathe machine were found, including fingers wrapped around the machine chuck, bram in the eye, electric shock. Welding machines were exposed to welding rays, welding sparks. Grinding machines are exposed to grinding stone fragments, excessive noise. scraping machines are cut by chisels, workpieces fall on the feet. For this reason, it is necessary to control hazards starting from elimination control by eliminating water sources around the welding area and substitution by replacing the manual method of lifting workpieces with Hoist. Engineering controls include installing machine guards, dust collectors, interlock systems. Administrative control by developing SOPs and SWPs, rotating work time and increasing machine maintenance schedules.